Hydrophobic surface modification of citrus fiber using octenyl succinic anhydride (OSA): Preparation, characterization and emulsifying properties. (November 2022) - Song, Ya-ting; Qi, Jun-ru; Yang, Xiao-quan; Liao, Jin-song; Liu, Zi-wei; Ruan, Cheng-wei
Abstract: We reported herein the modification of fiber acquired from citrus processing residue via the esterification with octenyl succinic anhydride. OSA-CF with degree of substitution (DS) of 0.904–0.103 were obtained. The chemical compositions of fiber were changed in pectin content. The hydration properties of the fiber increased significantly with the esterification reaction, especially the water holding capacity (WHC) increased from 12.42 g/g to 17.23 g/g. OSA-CF has more negative charge than CF since the exposure of hydrophilic group and addition of carboxyl (-COO - ). FT-IR spectrum of the OSA-CF at 1734 cm −1 revealed characteristic absorption peaks of the ester carbonyl groups (CO). Compared to original fiber, OSA-CF showed higher crystallinity and slightly lower thermal stability from the XRD, TG and DTG patterns. It can be seen from the scanning electron microscope (SEM) image that the surface of OSA-CF has more fold and porous structure. Meanwhile, emulsion prepared by OSA-CF showed superior emulsifying abilities such as higher emulsifying activity index (EAI) and emulsifying stability (ES) and smaller particle size. In conclusion, OSA esterification did improve the physicochemical properties and change chemical composition of fiber. Graphical abstract: The purposed mechanism and characterization for surface modification of citrus fiber using octenyl succinic anhydride (OSA). Image 1 Highlights: The original water holding capacity of citrus fiber was retained. Octenyl succinate citrus fiber ester (OSA-CF) displayed higher emulsifying capacities. OSA-CF has more surface negative charge. The carbonyl group (CO) decreased first and then increased. OSA-CF has more folds and deeper pore structure.